The influence of word of mouth digital marketing and service quality on buying interest halal skincare - Aura Kusuma; Muhammad Sholahuddin (Institute of Computer Science (IOCS), 2023)
As the number of people increases, the number of providers or producers of these products and services increases, consumers are increasingly required to be selective in choosing and buying products that suit their needs. In making a purchase decision, a consumer will go through several stages, starting from searching for information about the product or service to be purchased, as well as alternatives or other choices of these products and services. This study attempts to identify the influence of word of mouth, digital marketing and service quality on purchase intention. Purposive sampling is used in this quantitative research method, which collects data from a sample of 98 respondents using a questionnaire. Multiple regression to analyze data. The study's result show that while Word of mouth has not significant impact on buying interest Skincare Halal, Digital marketing has a positive and significant impact on buying interest skincare halal and Service Quality has a positive and significant impact on buying interest. This finding provides insight for halal skincare companies that digital marketing and service quality play a role in consumer buying interest. The research contributes to the existing body of knowledge in the field of consumer behavior and marketing, specifically focusing on halal skincare products. It provides actionable insights for halal skincare companies to enhance their marketing and service approaches and ultimately increase their chances of attracting more customers.